The Antimicrobial Activity of Lactobacillus Acidophilus Against Intestinal and Foodborne Pathogens - Mehdi , Luma Yousif (Iraqi Journal of Science, 2021)
In this study, isolated of Lactobacillus acidophilus were evaluated for their antipathogenicbacterial activity. The antibacterial activity of the three isolated againstintestinal and food borne pathogenic bacteria in vitro was determined by Well’sDiffusion method, a total of three isolates of Lactobacillus acidophilus isolated fromten different brands of traditional yoghurts showed a various antibacterial activityagainst tested pathogenic bacterium, Cronobacter sakazakii isolated from stoolsamples was more sensitive to the inhibition(23mm)inhibtion zone than wereHelicobacter pylori that isolated from stool samples (16mm) inhibtion zone andClostridium perfringens that isolated from stool samples (15mm). These results mayprovide a basis for support therapies for the treatment of intestinal and foodbornepathogens.